P‐161: 89.3% Lifetime Elongation of Blue TTA‐OLED with Assistant Host. Issue 1 (May 2016) - Hsin, Meng-Hung; Lee, Chun-Yu; Chen, Yi-Chi; Chen, Peng-Yu; Chen, Yu-Hung; Lu, Hsueh-Hsing; Lin, Yu-Hsin; Lin, Bo-Yen; Lee, Ming-Zer; Chiu, Tien-Lung; Lin, Chi-Feng; Lee, Jiun-Haw
Abstract : Operation lifetime of a blue OLED exhibiting triplet‐triplet annihilation increased by 89.3% with the incorporation of 10% assistant host in the emitting layer, which increased diffusion length of singlet exciton, reduced the quenching of triplet exciton, and blocked the triplet pair diffusion.